Healthcare-seeking behaviors for common childhood illnesses and associated factors among mothers/caretakers of under-five children in Haro Limu district, East Wollega, Oromia, Ethiopia: a cross-sectional study - Oljira, Shibru Fekadu; Merdassa, Emiru; Desalegn, Zelalem; Desalegn, Markos (Frontiers in Public Health, 2025)
BackgroundHealthcare has gained increasing significance in the quest to achieve a healthy society. Timely healthcare-seeking can help reduce child mortality rates. In many developing countries, the health of children is closely tied to the healthcare-seeking behavior of their mothers/caretakers.ObjectiveThis study aimed to assess the prevalence of healthcare-seeking behavior among mothers/caretakers for common childhood illnesses and to identify the associated factors in Haro Limu, East Wollega, Western Ethiopia, in 2019.MethodsA community-based cross-sectional study was conducted from 20 July to 30 September 2019 in the Haro Limu district. The required sample size was 459 mothers/caretakers of children under 5 years of age who had experienced a common childhood illness within the 4 weeks preceding the study. A multistage random sampling technique was used to select the study participants. Data were collected by health extension workers (HEWs) through face-to-face interviews using a structured questionnaire. The collected data were entered into EpiData (version 3.02) and exported to Statistical Package for the Social Sciences (SPSS) (version 20) for analysis. Binary logistic regression analysis was performed to identify the factors associated with healthcare-seeking behavior. The findings are presented using tables, pie charts, bar graphs, and narrative text.ResultsA total of 459 mothers/caregivers were included in this study, achieving a 100% response rate. Among children under 5 years who had experienced a common childhood illness within the 4 weeks preceding the survey, 68% (95% CI:65–71.1%) sought care from health facilities. Perceived severity of illness (AOR = 4.23, 95% CI: 2.27, 7.88), husband’s education level of secondary or higher (AOR = 2.70, 95% CI: 1.29, 5.64), and belonging to the richest household category (AOR = 2.40, 95% CI: 1.06, 5.44) were identified as independent predictors of the healthcare-seeking behavior of mothers/caretakers.ConclusionA considerable proportion of respondents did not seek care for their sick children at health facilities. It is essential to educate families and raise awareness in the community regarding the importance of seeking healthcare.